Myocardial Infarction by Percutaneous Embolization Coil Deployment in a Swine Model - Martínez-Falguera, Daina; Fadeuilhe, Edgar; Teis, Albert; Aranyo, Julia; Adeliño, Raquel; Bisbal, Felipe; Rodriguez-Leor, Oriol; Gálvez-Montón, Carolina (Journal of visualized experiments, 2021)
Myocardial infarction (MI) is the leading cause of mortality worldwide. Despite the use of evidence-based treatments, including coronary revascularization and cardiovascular drugs, a significant proportion of patients develop pathological left-ventricular remodeling and progressive heart failure following MI. Therefore, new therapeutic options, such as cellular and gene therapies, among others, have been developed to repair and regenerate injured myocardium. In this context, animal models of MI are crucial in exploring the safety and efficacy of these experimental therapies before clinical translation. Large animal models such as swine are preferred over smaller ones due to the high similarity of swine and human hearts in terms of coronary artery anatomy, cardiac kinetics, and the post-MI healing process. Here, we aimed to describe an MI model in pig by permanent coil deployment. Briefly, it comprises a percutaneous selective coronary artery cannulation through retrograde femoral access. Following coronary angiography, the coil is deployed at the target branch under fluoroscopic guidance. Finally, complete occlusion is confirmed by repeated coronary angiography. This approach is feasible, highly reproducible, and emulates the pathogenesis of human non-revascularized MI, avoiding the traditional open-chest surgery and the subsequent postoperative inflammation. Depending on the time of follow-up, the technique is suitable for acute, sub-acute, or chronic MI models.